2022
DOI: 10.1155/2022/1225253
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Transcutaneous Acupoint Electrical Stimulation on Cancer‐related Fatigue and Negative Emotions in Cancer Patients: A Systematic Review and Meta‐Analysis of Randomized Controlled Trials

Abstract: Transcutaneous electrical acupoint stimulation (TEAS) is a noninvasive and therapeutic technique that stimulated the acupoint by delivering electricity. Whether TEAS could relieve cancer-related fatigue (CRF), anxiety, and depression and improve the quality of life in cancer patients remains controversial. Thus, we conducted a thorough literature search of electronic Chinese and English databases for randomized controlled trials (RCTs) reporting the effect of CRF, anxiety, depression, and quality of life in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Some studies have found that acupuncture can effectively regulate emotional changes and cognitive dysfunction. 39 In addition, this study observed the changes of metabolites closely related to CRF, and more objectively evaluated the intervention effect of MRA on CRF. The underlying mechanism of acupuncture therapy may be related to regulating mitochondrial function, coordinating nervous system activity, regulating neurotransmitter production and alleviating immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that acupuncture can effectively regulate emotional changes and cognitive dysfunction. 39 In addition, this study observed the changes of metabolites closely related to CRF, and more objectively evaluated the intervention effect of MRA on CRF. The underlying mechanism of acupuncture therapy may be related to regulating mitochondrial function, coordinating nervous system activity, regulating neurotransmitter production and alleviating immune response.…”
Section: Discussionmentioning
confidence: 99%